Marginalization and Reform of Religion - Zohaib Ahmad (Journal of Islamic Thought and Civilization, 2019)
The term marginalization is often used for a community or group which is pushed to the edges of the society through certain social, political, and/or religious restrictions. The history of German Jews and Muslims of the Indian subcontinent stands witness that, to varying degrees over time, they were bound to live on the edges of their respective societies. This discrimination was not just because of their different social, cultural, and political status but religion was also a major factor behind it. In such conditions, Moses Mendelssohn and Syed Ahmad Khan worked for the betterment of their respective Jewish and Muslim communities. Although the work of both scholars is a recurring theme of discussion in the academic world, still there is no study available in which their efforts have been compared. By presenting a feature by feature comparison of the works of both scholars, the current paper first figures out their methodology and then explores their motive behind using pure reason to interpret sacred scriptures. It is also argued that there are fewer differences and more commonalities in their works. Their primary aim was to equip their people with modern education, since they thought that through educational reform they would be able to improve the social, political, and economic conditions of their people. Although they achieved noteworthy success, their efforts changed the religious direction of their people. Especially after the reform of Mendelssohn, a significant number of Jews distanced themselves from their ancestral religion.